1995
DOI: 10.1068/p241165
|View full text |Cite
|
Sign up to set email alerts
|

A New Motion Illusion Related to the Aperture Problem

Abstract: A previously unreported motion illusion is described. Oblique lines that drift smoothly on the retina in a vertical direction appear to be displaced laterally. The effect occurs both for moving lines under fixation and for stationary lines under ocular tracking of an external target. Orientation, length, and homogeneity of the obliques affect the magnitude of illusory displacement. We propose that this illusion is associated with a misregistration of the direction of displacement occurring, in lines slanted re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
4
10
1
Order By: Relevance
“…With a pattern of results consistent with those of Bressan and Vezzani’s visual motion illusion [13], we found that participants veered substantially away from straight ahead when walking over a patterned floor with oblique pattern orientations. We propose that the veering observed here is due to the aperture problem in motion perception [11] in the relatively restricted lower visual field, leading people to misperceive their own lateral location in space while traversing the walkway.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…With a pattern of results consistent with those of Bressan and Vezzani’s visual motion illusion [13], we found that participants veered substantially away from straight ahead when walking over a patterned floor with oblique pattern orientations. We propose that the veering observed here is due to the aperture problem in motion perception [11] in the relatively restricted lower visual field, leading people to misperceive their own lateral location in space while traversing the walkway.…”
Section: Discussionsupporting
confidence: 87%
“…In the human visual system, the aperture problem occurs whenever the detection of motion is carried out over a limited part of a scene such as in the lower visual field inherent for floor patterns. The effect can be easily visualised with a compelling motion illusion first described by Bressan and Vezzani [13]. In this illusion, visually tracking a dot that moves vertically between two stationary oblique lines makes the lines appear to move laterally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motion illusion in terms of oblique lines has been employed in different studies, such as for measuring the receptive field size of the motion detector, which underlie the aperture problem in motion perception , and for investigating the relationship between the magnocellular-dorsal stream and dyslexia (Gori et al, 2015). These motion illusions are based on the detection of illusory motion signals in viewing the oblique components, which drift smoothly on the retina (Bressan & Vezzani, 1995;Gori & Hamburger, 2006). Results of several studies have indicated that the processing of oblique components underlies motion illusions of different types, not only the Pinna illusion (Ichikawa et al, 2006;Pinna & Brelstaff, 2000) but also the Ouchi-Spillman illusion (Ashida, 2002;Fermu¨ller, Pless, & Aloimonos, 2000;Mather, 2000;Ouchi, 1977;Spillmann, 2013), Rotating-Tilted-Line illusion , Unchained-dot illusion (Gori, Giora, & Stubbs, 2010), illusion of direction for the moving matrices of oblique lines (Lorenceau, Shiffrar, Wells, & Castet, 1993), and nonrigid motion illusion with nonparallel oblique components (Kim & Papathomas, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The effects in almost all of the motion illusions caused by smooth retinal motion depend on the angles between the retinal motion direction and the detected motion direction (Bressan and Vezzani 1995; Fantoni and Pinna 2008; Gori and Yazdanbakhsh 2008; Ito et al 2009; Pinna and Brelstaff 2000). Some depend on the angles between the retinal motion direction and the orientation of the stimulus elements, eg, parallel (Khang and Essock 2000) or orthogonal (Pinna and Spillmann 2005, figure 9; Ito et al 2009, figure 5).…”
Section: Introductionmentioning
confidence: 99%